The Utilization of Interactive Video Technology in Learning Basic Locomotor Motion in Physical Education: Literature Review - Rosdiana Sartika; Padli Padli; Sepriadi Sepriadi; Nugroho Susanto (STKIP Singkawang, 2025)
Physical Education, Sports, and Health have an important role in developing students' motor skills, including the basic movement of the locomotor. However, challenges such as a lack of variety of learning methods and less attractive media often hinder the learning process. Research Objectives This article aims to review various literature related to the use of interactive video technology in learning basic locomotor movements in physical education at the elementary school level. Methods This study uses the literature review method by analyzing relevant articles, journals, and literature sources published in the last 10 years. The reviewed literature focuses on the development, implementation, and effectiveness of the use of interactive video media in learning basic locomotor motion. The results of the study show that interactive video technology has several advantages, such as providing clear visual demonstrations, improving students' understanding of the material, and encouraging active participation through interactive features such as quizzes or simulations. In addition, this media has been proven to be effective in improving student learning outcomes compared to conventional methods. Factors such as video design, teacher engagement, and the suitability of the material with the curriculum are important aspects that affect the success of implementation. The conclusion is that the use of interactive video technology in learning basic locomotor movements in physical education has a positive impact on the motivation, involvement, and learning outcomes of elementary school students. This study recommends the further development of interactive video-based learning media that is in accordance with the needs of students and the school curriculum